RANCANG BANGUN ALAT PENDETEKSI GAS CO DAN LPG BERBASIS IOT MENGGUNAKAN NODEMCU - Rian Zandy Armantya (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2022)
Air pollution is a problem that causes a decrease in air quality and has a negative impact on human health. A monitoring system is needed to determine pollutant levels below the threshold. LPG gas can help cooking activities in the community because it is easy to use. However, LPG gas can also be harmful to people in cooking since CO gas comes from combustion fumes can cause air pollution. The MQ-6 sensor can detect LPG gas that exceeds the limit, and the MQ-7 sensor can detect CO gas that causes air pollution from incomplete combustion fumes. The research method used the waterfall and black-box testing methods. The IoT-based CO and LPG gas detection system using nodemcu and is described in a flowchart diagram. The research aims to create a gas detection monitoring system by utilizing the internet and notification of data obtained in real-time. The device testing results run smoothly, and there were no errors as well as the tool was successfully designed and implemented. LPG gas that exceeds the limit will have an alarm notification from the buzzer, and CO gas that exceeds the limit will turn on the fan. Commands from the device after receiving the data will be sent online using the telegram application.